Getting-satellite-data: a module designed for easily extracting satellite data features for crop monitoring - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The tool is available in GitHub, it has several examples and its functions are documented for going through in an easy and friendly way. Taking advantage of its coding properties, we were able to develop a module in our data capture tool, to integrate satellite data in our analysis.